A novel dual-parameter method for evaluating seismic collapse severity in masonry pagodas - Mingdong Li; Junlong Lu; Defa Wang; Xin Jia; Xiaoqin Wu; Dongxu Mao; Zuoyi Yun; Zhenshan Wang (Bulletin of Earthquake Engineering, 2026)

Water Injection Failure of Full-Ocean-Depth Adjustable Ballast System: Mechanism Analysis and Experimental Verification - Zhida Chen; Sheng Zhou; Jize Jiang; Linglong Li; Cong Ye; Shuai Liu; Defa Wu; Yunxiang Ma; Lang Gu (Journal of Marine Science and Engineering, 2026)
Reliable operation of adjustable ballast systems is essential for full-ocean-depth manned submersibles, but existing studies mostly focus on component-level performance optimization, leaving the multi-valve coupled instability mechanism under ultra-high pressure insufficiently understood. This paper investigates an uncontrolled water injection failure in the adjustable ballast system of the “Fendouzhe” submersible via fault tree analysis, high-pressure physical tests and AMESim dynamic simulations. Results show that the initial fit clearance of the downstream flow valve is the dominant prerequisite for instability, and a fluid–structure interaction positive feedback loop between the series valve assembly drives the flow surge fault. Removing the series flow valve fundamentally interrupts the coupling feedback loop. Full-range 0–115 MPa bench tests and follow-up sea trials confirm that the modified system eliminates the observed flow surge within the tested pressure range and operating conditions. This work provides a practical diagnostic framework and engineering reference for reliability design of high-pressure seawater hydraulic systems.

Triterpenoid saponins from Caragana korshinskii Kom.: α ‑glucosidase inhibitory activity and characterisation of four new compounds - Yumei Ma; Tao Chen; Zhibo Song; Hailun Feng; Defa Kong; Juyuan Luo; Shuo Wang; Cheng Shen; Yulin Li (Natural Product Research, 2026)

Spiral wrapped in-situ optic fiber tract - Hai Fu; Huifeng Yang; Xin Qiu; Zhi Chen; Yao Zhu; Defa Li; Han Zhang; Zhongjian Xie (Chemical Engineering Journal, 2026)

Corrigendum to “Analysis and optimization of opening characteristics of deep-sea water hydraulic safety valve” [Ocean Eng. 344, 15 (January 2026), 123682] - Jize Jiang; Jiefu Liu; Jiangxiong Li; Boyang Zhang; Xiguang Hu; Yinshui Liu; Defa Wu (Ocean Engineering, 2026)

Analysis and optimization of opening characteristics of deep-sea water hydraulic safety valve - Jize Jiang; Jiefu Liu; Jiangxiong Li; Boyang Zhang; Xiguang Hu; Yinshui Liu; Defa Wu (Ocean Engineering, 2026)

Theoretical and experimental study on the performance of the hydraulic power unit employed on full ocean depth manned submersible - Zhida Chen; Tianhao Li; Linglong Li; Jincang Liao; Cong Ye; Defa Wu; Shuai Liu; Yinshui Liu; Yunxiang Ma; Lang Gu; Gang Sun (Ocean Engineering, 2025)

Single-electrode multiplex sensing via metal ion displacement method - Yiming Zhang; Zhi Chen; Songrui Wei; Huiling Lin; Yujun Zhang; Yingxia Liu; Jing Wang; Qi Gao; Defa Li; Han Zhang; Zhongjian Xie (Chemical Engineering Journal, 2025)

An investigation of scouring mechanism and equilibrium state by the submerged jet using synthesized oblique velocity - Xiguang Hu; Zhida Chen; Xing Yang; Linglong Li; Defa Wu; Yunxiang Ma; Yinshui Liu (Ocean Engineering, 2025)

Bamboo-derived nitrogen-doping magnetic porous hydrochar coactivated by K2FeO4 and CaCO3 for phenol removal: Governing factors and mechanisms - Tao Pei; Feng Shi; Can Liu; Yi Lu; Xu Lin; Defa Hou; Shunxiong Yang; Jirong Li; Zhifeng Zheng; Yunwu Zheng (Environmental Pollution, 2023)

Preparation of nitrogen-containing compounds and nitrogen-doped biochar via nitrogen-rich pyrolysis coupled with ammonia source impregnation - Donghua Li; Meihua Fu; Tao Pei; Yi Lu; Can Liu; Xu Lin; Defa Hou; Hao Sun; Cuiping Luo; Zhifeng Zheng; Yunwu Zheng (Journal of Environmental Chemical Engineering, 2023)

Comparison of the Variability of Small Extracellular Vesicles Derived from Human Liver Cancer Tissues and Cultured from the Tissue Explants Based on a Simple Enrichment Method - Jie Chen; Zhigang Jiao; Jianwen Mo; Defa Huang; Zhengzhe Li; Wenjuan Zhang; Tong Yang; Minghong Zhao; Fangfang Xie; Die Hu; Xiaoxing Wang; Xiaomei Yi; et al. (Stem Cell Reviews and Reports, 2022)
A potential use of small extracellular vesicles (sEVs) for diagnostic and therapeutic purposes has recently generated a great interest. sEVs, when purified directly from various tissues with proper procedures, can reflect the physiological and pathological state of the organism. However, the quality of sEV is affected by many factors during isolation, including separation of sEV from cell and tissues debris, the use of enzymes for tissue digestion, and the storage state of tissues. In the present study, we established an assay for the isolation and purification of liver cancer tissues-derived sEVs (tdsEVs) and cultured explants-derived sEVs (cedsEVs) by comparing the quality of sEVs derived from different concentration of digestion enzyme and incubation time. The nano-flow cytometry (NanoFCM) showed that the isolated tdsEVs by our method are purer than those obtained from differential ultracentrifugation. Our study thus establishes a simple and effective approach for isolation of high-quality sEVs that can be used for analysis of their constituents. Graphical abstract

Metabolic characteristics and nutrient utilization in high-feed-efficiency pigs selected using different feed conversion ratio models - Beibei He; Tiantian Li; Wei Wang; Hang Gao; Yu Bai; Shuai Zhang; Jianjun Zang; Defa Li; Junjun Wang (Science China Life Sciences, 2019)

S-Adenosylmethionine-induced adipogenesis is accompanied by suppression of Wnt/β-catenin and Hedgehog signaling pathways - Yang Liu; Wentao Lv; Boyang Yu; Tingting Ju; Feiyun Yang; Meihua Jiang; Zuohua Liu; Ling Xu; Wenjuan Sun; Jinxiu Huang; Defa Li; Jingdong Yin (Molecular and Cellular Biochemistry, 2013)

S-adenosylmethionine stimulates fatty acid metabolism-linked gene expression in porcine muscle satellite cells - Tao Yue; Qian Fang; JingDong Yin; DeFa Li; Wei Li (Molecular Biology Reports, 2010)

Oct-1 functions as a transactivator in the hormonal induction of β-casein gene expression - Bing Dong; Chengfei Huang; Defa Li; Feng-Qi Zhao (Molecular and Cellular Biochemistry, 2009)

Screening of Bacillus strains as potential probiotics and subsequent confirmation of the in vivo effectiveness of Bacillus subtilis MA139 in pigs - Xiaohua Guo; Defa Li; Wenqing Lu; Xiangshu Piao; Xiaoling Chen (Antonie van Leeuwenhoek, 2006)

Screening and characterization of astaxanthin-hyperproducing mutants of Haematococcus pluvialis - Yong Chen; Defa Li; Wenqing Lu; Jianjun Xing; Bodi Hui; Yashan Han (Biotechnology Letters, 2003)